2016
DOI: 10.1002/anie.201600856
|View full text |Cite
|
Sign up to set email alerts
|

Controlled‐Potential Electromechanical Reshaping of Cartilage

Abstract: An alternative to conventional "cut-and-sew" cartilage surgery, electromechanical reshaping (EMR) is a molecular-based modality in which an array of needle electrodes is inserted into cartilage held under mechanical deformation by a jig. Brief (ca. 2 min) application of an electrochemical potential at the water-oxidation limit results in permanent reshaping of the specimen. Highly sulfated glycosaminoglycans within the cartilage matrix provide structural rigidity to the tissue through extensive ionic-bonding n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Previous studies in our lab have demonstrated collagen structural change in the rabbit cartilage and pig skin [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. This study is the first to characterize the redoxinduced alteration in the optical and mechanical behavior in the human skin.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous studies in our lab have demonstrated collagen structural change in the rabbit cartilage and pig skin [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. This study is the first to characterize the redoxinduced alteration in the optical and mechanical behavior in the human skin.…”
Section: Introductionmentioning
confidence: 75%
“…These ions create a steep pH gradient around the electrodes, which lead to localized stress relaxation and shape change, a process we refer to as electromechanical reshaping (EMR) [27,28]. Through a series of studies, we demonstrated the safety and efficacy of this approach to reshape cartilage [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. During these in vivo EMR studies in rabbits, changes in skin texture were incidentally observed around the non-insulated needle-insertion sites [12,15,24].…”
Section: Discussionmentioning
confidence: 99%
“…Although the concept of ECT is derived from previous studies 1,4,5,8,19,20 on electrochemical effects in cartilage, the present study characterizes the redox-induced alteration in the optical and mechanical behavior in skin. A previous study 1 suggests that the electrochemical reactions that are triggered are related to the hydrolysis of water, which produces a localized pH perturbation that drives hydrogen and hydroxide ions into the tissue. More than half a century of detailed clinical experience has already demonstrated how topical application of acid to the skin (ie, chemical peels) alters appearance and texture for beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 1,17 have specifically examined the effects that surround the electrodes, including pH mapping in cartilage. Furthermore, other studies 4,8,20,28,29 have used EMR to mimic procedures that emulate the classic cut and suture operation ex vivo and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation